2022
DOI: 10.1177/15588661211052077
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Faced and Solutions Implemented in Response to the COVID-19 Pandemic among North American College Campus Recreation Staff

Abstract: The COVID-19 pandemic has had a significant impact on the operation and availability of campus recreation services at North American colleges and universities. This study examined the challenges faced and solutions implemented by campus recreation departments as a result of the COVID-19 pandemic from the perspective of campus recreation staff from across North America. Institution and staff characteristics along with challenges and solutions were collected from 174 campus recreation department staff via an onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Relative to the latter, private or female only workout spaces could help to reduce constraints associated with harassment or intimidation from male users, helping to address the physical activity comfort priority identified in the 'concentrate here quadrant' (Austin Robert Anderson et al, 2020;Carter-Francique, 2011;Hoang et al, 2016;Shaikh et al, 2018;Stankowski et al, 2017;. Moreover, many universities have developed facility/equipment reservation systems during the COVID-19 pandemic that could be leveraged for scheduling private workout spaces in advance (Powers et al, 2022b). Reservations systems could support physical activity prioritization, an important strategy for negotiating constraints to physical activity at campus recreation centers (Powers et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative to the latter, private or female only workout spaces could help to reduce constraints associated with harassment or intimidation from male users, helping to address the physical activity comfort priority identified in the 'concentrate here quadrant' (Austin Robert Anderson et al, 2020;Carter-Francique, 2011;Hoang et al, 2016;Shaikh et al, 2018;Stankowski et al, 2017;. Moreover, many universities have developed facility/equipment reservation systems during the COVID-19 pandemic that could be leveraged for scheduling private workout spaces in advance (Powers et al, 2022b). Reservations systems could support physical activity prioritization, an important strategy for negotiating constraints to physical activity at campus recreation centers (Powers et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Data collected by the survey covered a range of topics including: campus recreation policies, programs and practices; diversity, equity, and inclusion; and the impact of the pandemic on campus recreation staff/departments. This study focuses exclusively on the equity related topics, with pandemic related findings reported in a prior study (Powers et al, 2022b). All equity related questions instructed to participants to answer questions as they would prior to the pandemic, as opposed to in the mist of the pandemic.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Zhang et al's study (2004) found that mid-level campus recreation employees experienced such as inadequate compensation and changing job roles. In addition, Powers et al's (2022) study on campus recreation employees’ experiences during the pandemic highlighted that employees experienced adjusted job responsibilities, new safety protocols, and budget cuts.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Universities and colleges did not avoid the impacts of the pandemic, resulting in many institutions' temporary closures and reopenings (Powers et al, 2022). As such, campus recreation departments also experienced these temporary closures and reopenings (NIRSA, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation